Legitimacy and context: Implications for public sector reform in developing countries - Andrews, Christina W. [UNESP] (John Wiley & Sons Ltd, 2008)
This article examines the interplay between legitimacy and context as key determinants of public sector reform outcomes. Despite the importance of variables Such as legitimacy of public institutions, levels of civic morality and socio-economic realities, reform strategies often fail to take such contextual factors into account. The article examines, first, relevant literature both conceptual and empirical, including data from the World Values Survey project. It is argued that developing countries have distinctive characteristics which require particular reform strategies. The data analysed shows that in Latin American countries, there is no clear Correlation between confidence in public institutions and civic morality. Other empirical studies show that unemployment has a negative impact on the level of civic morality, while inequality engenders corruption. This suggests that poorer and socio-economically stratified countries face greater reform challenges owing to the lack of legitimacy of public institutions. The article concludes that reforms should focus on areas of governance that impact on poverty. This will in turn help produce more stable outcomes. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: public administration; legitimacy; public sector reforms; developing countries